Biegły psycholog wobec tezy o niezdolności psychicznej do podjęcia istotnych obowiązków małżeńskich. Analiza przypadku - Nowicka, Urszula (Ius Matrimoniale, 2018)
Proceedings regarding the nullity of marriage for causes of a psychic nature require the assistance of experts. The subject of the study is the analysis of the opinion issued in the case of the nullity of marriage in the church court in W. It is an example of a competent opinion. It takes into account the principles of Christian anthropology, distinguishes between natural human traits and psychical disorders, avoids all kinds of automatism, determinism and syllogism in the assessment of human personality, rejects characterological differences as the basis for reviewing in processes.